Life in Extreme Environments 2006
DOI: 10.1007/978-1-4020-6285-8_13
|View full text |Cite
|
Sign up to set email alerts
|

Life strategy, ecophysiology and ecology of seaweeds in polar waters

Abstract: Polar seaweeds are strongly adapted to the low temperatures of their environment, Antarctic species more strongly than Arctic species due to the longer cold water history of the Antarctic region. By reason of the strong isolation of the Southern Ocean the Antarctic marine flora is characterized by a high degree of endemism, whereas in the Arctic only few endemic species have been found so far. All polar species are strongly shade adapted and their phenology is finely tuned to the strong seasonal changes of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
1
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 194 publications
2
51
1
7
Order By: Relevance
“…Benthic marine communities along the northern half of the western Antarctic Peninsula (WAP) possess rich and diverse assemblages of macroalgae and invertebrates (De Broyer et al 2014). Predominantly brown but also many red macroalgae dominate shallow benthic communities on hard substrates along the WAP, often covering over 80% of the seafloor with standing biomass levels similar to those in temperate kelp forests (Wiencke & Amsler 2012, Wiencke et al 2014). Several species of large, perennial brown algae are particularly abundant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benthic marine communities along the northern half of the western Antarctic Peninsula (WAP) possess rich and diverse assemblages of macroalgae and invertebrates (De Broyer et al 2014). Predominantly brown but also many red macroalgae dominate shallow benthic communities on hard substrates along the WAP, often covering over 80% of the seafloor with standing biomass levels similar to those in temperate kelp forests (Wiencke & Amsler 2012, Wiencke et al 2014). Several species of large, perennial brown algae are particularly abundant.…”
Section: Introductionmentioning
confidence: 99%
“…These include Desmarestia menziesii J. Agardh and/or Desmarestia anceps Montagne that typically dominate biomass in shallower waters down to approximately 10–15 or 20 m, with Himantothallus grandifolius (A. Gepp & E.S. Gepp) Zinova dominating from 10–15 or 20 m down to 30 or 40 m, or sometimes even greater depths (Wiencke & Amsler 2012, Wiencke et al 2014). It is common to find one or two of these three species of brown algae covering nearly 100% of the benthos in some locations.…”
Section: Introductionmentioning
confidence: 99%
“…However, sporophytes were held for unequal periods of 0 to 6 days in the storage containers before spore release was induced, which might have led to an acclimation of the collected material to storage conditions as storage conditions were different from conditions at the natural growth site with respect to radiation conditions and biotic influences. Adjustments to light regime (Beale and Appleman 1971;Ramus et al 1976;Falkowski and LaRoche 1991;Brey 2009), nutrient availability (Aguilera et al 2002) or season (Wiencke et al 2007b) are well documented in seaweeds but less well for spores. Furthermore, Wiencke et al (2007a) suggested that parental adaptations might be mirrored in spores.…”
Section: Spore Responsesmentioning
confidence: 99%
“…Algae inhabiting the polar latitudes are characterized by the structural features and resilience that allow them to exist in harsh environmental conditions, in particular, they have strongly pronounced resistance to cold and darkness [2]. Despite these BRDEM-2019 peculiarities, their biomass is extremely low, and the climatic changes significantly affect the algal communities in the polar latitudes [3].…”
Section: Introductionmentioning
confidence: 99%